Capturing Business Opportunities In The Sports Industry With An Integrated Technology Approach - Mohamad Rizal, Rony; Juditya, Silvy; Komarudin, Diky; Kurniawan Miraz, Rifky (STKIP Paasundan Press, 2025)
This research aims to examine the application of integrated technology in the fitness industry at Allday Fitness in Soreang to improve operational efficiency and customer experience as well as capture new business opportunities. This research employed a qualitative methodology, utilizing a case study approach, and involved in-depth interviews, participatory observation, and documentation. The results showed that the use of technologies such as mobile fitness applications, IoT-based fitness monitoring devices, and cloud computing-based management systems was able to improve operational efficiency and enrich the customer experience. In addition, AI-based service personalization and the development of online community platforms create business opportunities that drive customer loyalty and engagement. Regular training and strategic partnerships can overcome constraints such as limited staff skills and investment costs. This research confirms the importance of technology as a strategic asset that supports innovation and business growth in the fitness industry.